Assessment Of Mosquito Larvae Density In Eziobodo Community, Owerri-West L.G.A, Imo State - Udujih, Obinna Godwin; Udujih, Helen Ifeoma; Ofor, Oluchi; KenechukwuDozie, Queen Ogechi; Dozie, Ugonma Winie (European Journal of Applied Sciences, 2021)
Larval control is of paramount importance in the reduction of malaria vector abundance and subsequent disease transmission reduction. This study is aimed at assessing mosquito larvae density and profile in Eziobodo community, Owerri West L.G.A. Imo State. Standard dipping techniques was used to determine larval density, morphological characteristic was used to determine the larvae genera, aquatic quality condition and habitat preferences were observed at the oviposition sites. A plastic dipper of 50mls was used to collect water samples from ground puddles, plastic containers, earthen pots, gutters, tin cans and old car tires. The result showed the presence of Anopheline larvae 63 (42.0%), and Culicine larvae 88(58.0%). Anopheles larvae were found mostly in surface and shallow water with semi shaded light whereas Culicine larvae were found in equal density in both shallow and deep water preferably with semi shaded and shaded light. Residents used sanitation measures mainly for mosquito control closely followed by Insecticide treated bed nets (ITNs). Some (30%) reported the use of a combination of sanitation, ITNs, insecticide sprays/coils. Understanding larval habitat and its ecology in different environments can give an insight for control of mosquito borne diseases. Community participation to improve their sanitation will help to close ground puddles, clean gutters, removal of old car tires that can serve as breeding sites of mosquitoes.